APRESIASI SASTRA DAN KRITIK DRAMA TRADISIONAL DAN MODERN: KAJIAN LINTAS ANGKATAN 1920, 1933, 1945, HINGGA 2000-AN - Atika Wasilah; Faza Najmul Pasha; Fifi Amelia Sitinjak; lumbangaol nurcahaya; Oni Catrine Joana Simbolon; Sion Katarina Situmorang; Tiana Silalahi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the development of literary appreciation and dramatic criticism in Indonesian literature from the 1920s generation through the 2000s, employing a historical-critical approach and reception theory. The study focuses on how each literary generation responded to its respective social, political, and cultural conditions through dramatic works, and how literary criticism reflected those responses as expressions of aesthetic and ideological values. A literature review method was employed, drawing on primary sources including dramatic texts and critical documents, as well as secondary sources comprising journal articles and academic books published within the last decade. Findings indicate that each generation constructed distinct aesthetic conventions: the 1920s generation relied on Malay-Western literary traditions; the 1933 generation introduced social realism as a response to colonialism; the 1945 generation emphasized post-war universal humanism; while contemporary drama of the 2000s is characterized by formal experimentation, cultural hybridity, and narrative fragmentation. These findings demonstrate that Indonesian dramatic criticism cannot be separated from its sociohistorical context and the evolving dynamics of public reception. Theoretical implications reinforce the argument that literary appreciation is inherently contextual and relational, while practical implications are relevant to curriculum development and dramatic work evaluation in Indonesia.